Multiplex polymerase chain reaction for the simultaneous detection of Mycoplasma pneumoniae, Chlamydia pneumoniae, and Chlamydia psittaci in respiratory samples. Issue 4 (1st April 1999) - Tong, C Y; Donnelly, C; Harvey, G; Sillis, M
Abstract : AIMS: To develop a multiplex polymerase chain reaction (PCR) for the simultaneous detection of Mycoplasma pneumoniae, Chlamydia pneumoniae, and Chlamydia psittaci in respiratory samples. METHODS: Oligonucleotide primers for the amplification of the DNA of these three organisms were optimised for use in combination in the same reaction. PCR products were detected by hybridisation with pooled internal probes using an enzyme linked immunosorbent assay. Those with positive signals were further differentiated using species specific probes. Quality of DNA extraction and PCR inhibition were controlled by amplification of a human mitochondrial gene. A panel of 53 respiratory samples with known results was evaluated blindly. This was followed by a retrospective study on sputa collected from 244 patients with suspected community acquired pneumonia. RESULTS: The multiplex assay had a lower sensitivity than PCR with individual primers by about one log. The resultant sensitivity was considered acceptable for diagnostic use. Of the panel of 53 samples, nine of 11 M pneumoniae, 11 of 11 C pneumoniae, six of seven C psittaci, and 24 of 24 negative samples were correctly identified. Of the 244 patients with pneumonia, seven (2.9%) had detectable M pneumoniae, six (2.5%) had C pneumoniae, and one (0.4%) had C psittaci. The case notes from 11 patients were studied. The PCR finding was of possible significance in at least eight of these patients. CONCLUSIONS: This multiplex PCR assay has the potential to be used as a diagnostic and epidemiological tool. Further prospective studies are needed to establish its clinical value.